Structural, optical, electrical and dielectric properties of (Sr1-xMgx)(Sn0.5Ti0.5)O3 (X=0.00, 0.25, 0.50, 0.75) ceramics via solid state route. Issue 21 (1st November 2021) - Abbas, Mujahid; Ullah, Rafi; Ullah, Kamran; Sultana, Fozia; Mahmood, Aamir; Mateen, Abdul; Zhang, Yuefei; Ali, Asad; Althubeiti, Khaled; Mushtaq, Muhammad; Zaman, Abid
Abstract: We have prepared (Sr1-x Mgx )(Sn0.5 Ti0.5 )O3, (X = 0.00, 0.25, 0.50, 0.75) samples by the solid state reaction method and studied the structural, optical, electrical modulus and the other dielectric properties of the samples with respect to variation in frequencies (1 × 10 9 to 2 × 10 9 Hz) using Impedance Analyzer. This study suggests that the XRD patterns of the samples have shown that this possesses cubic perovskite structure in space group Pm-3m and scanning electron microscope was used to analyze the grain size distribution and porosity of the ceramic. The dielectric properties of these materials were strongly dependent upon on concentration X as well as amount of frequencies. The existence of metal oxygen bonds of Sr–Ti–O was verified by Fourier Transform Infra Red (FTIR) spectrum at 540 cm −1 . The highest PL intensity of 716.38 that exhibits the green emission (508.5 nm) was obtained for the composition of (Sr0.25 Mg0.75 )(Sn0.5 Ti0.5 )O3 . AC conductivity slowly decreases with increasing Mg substitution and also the sample (Sr0.25 Mg0.75 )(Sn0.5 Ti0.5 )O3 having the lowest (constant) value of conductivity at 1 GHz–2GHz.